Croatian in Contact with European Languages: Modelling Contact-Induced Change - Sočanac, Lelija (Array, 2004)
The poster presents contacts between Croatian and six European languages: Italian, Hungarian, German (close/historical contacts) and French, Russian and English (distant/modern contacts). The analysis takes into account parameters such as language typology and relationship ; the time of significant contact ; contiguity ; the social and cultural position of the languages in contact ; the literary, political and religious status of the languages involved and language attitudes.